2016
DOI: 10.1155/2016/6178921
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Interleukin-6 in Papillary Thyroid Carcinoma

Abstract: This study sought to reveal the significance of IL-6 in papillary thyroid carcinoma by determining its circulating levels, tumoral protein, and mRNA expressions. As compared to the healthy individuals, serum IL-6 was significantly higher in patients with benign thyroid diseases and PTC. Further, its level was significantly higher in PTC patients as compared to patients with benign thyroid diseases. ROC curves also confirmed a good discriminatory efficacy of serum IL-6 between healthy individuals and patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 72 publications
5
44
2
2
Order By: Relevance
“…We cannot therefore draw conclusions on whether adiponectin plays a role in TC in addition to or independently of excess weight. A number of relatively small studies have compared levels of leptin, circulating cytokines, including IL‐1β, IL‐5, IL‐6, IL‐7, IL‐8, IL‐9, IL‐10, IL‐13, TNF‐α, IFN‐γ and CRP, among TC cases and controls but results were not consistent across studies . In prediagnostic samples, we observed no significant associations with leptin, CRP, IL‐6 and TNF‐α.…”
Section: Discussioncontrasting
confidence: 83%
“…We cannot therefore draw conclusions on whether adiponectin plays a role in TC in addition to or independently of excess weight. A number of relatively small studies have compared levels of leptin, circulating cytokines, including IL‐1β, IL‐5, IL‐6, IL‐7, IL‐8, IL‐9, IL‐10, IL‐13, TNF‐α, IFN‐γ and CRP, among TC cases and controls but results were not consistent across studies . In prediagnostic samples, we observed no significant associations with leptin, CRP, IL‐6 and TNF‐α.…”
Section: Discussioncontrasting
confidence: 83%
“…2). The cytokines IL-6 and IL-8 are involved in angiogenesis and progression in different cancer types [52-54]. On the RPM, their genes were up-regulated significantly after 4 h in RPM-AD cells.…”
Section: Discussionmentioning
confidence: 99%
“…1. Eighteen of these 29 studies are published in Chinese [14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and the rest are published in English [33][34][35][36][37][38][39][40][41]. Nineteen studies were conducted in China, two in India and two in Turkey.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the 29 included studies, 9 reported the level of serum IL-6 in patients with thyroid carcinoma and control subjects [20,23,28,32,[35][36]38,[40][41]. Due to the large heterogeneity of the merged SMD 7 values of serum IL-6 level by the heterogeneity analysis (heterozygosity test, Chi 2 =334.36, P<0.00001, I 2 = 96%), random-effect model was used to pooled the SMD values, and the pooled effect size in favor of control subjects is 1.04 (95% CI 0.40 to 1.67, P=0.001) ( Fig.…”
Section: Il-6 and Thyroid Carcinomamentioning
confidence: 99%